Multi-scale convolutional recurrent neural network for psychiatric disorder identification in resting-state EEG - Yan, Weizheng; Yu, Linzhen; Liu, Dandan; Sui, Jing; Calhoun, Vince D.; Lin, Zheng (Frontiers in Psychiatry, 2023)
Background: Accurate classification based on affordable objective neuroimaging biomarkers are important steps toward designing individualized treatment. Methods: In this work, we investigated a deep learning classification model, multi-scale convolutional recurrent neural network (MCRNN), to explore psychiatric disorder-related biomarkers by leveraging the spatiotemporal information of resting-state EEG (rsEEG) using a multiple psychiatric disorder database containing 327 individuals diagnosed with schizophrenia, bipolar, major depressive disorders and healthy controls. All subjects were mapped to a shared low-dimensional subspace for intuitively interpreting the inter-relationship and separation of psychiatric disorders. Results: Psychiatric disorders were identified using rsEEG with high accuracy ranged from 78.6% to 91.3% in patient vs controls 2-class classification, and 68.2% in 4-class classification. The control-to-schizophrenia trajectory interpretated by the model was consistent with the disease severity in clinical observation. Conclusion: The MsRNN demonstrated a capability in extracting discriminative rsEEG biomarkers for psychiatric disorder classification, indicating its potential to facilitate our understanding of psychiatric disorders and monitoring interventions.